METHOD FOR ADSORPTION PURIFICATION OF ASSOCIATED OIL GASES FROM MERCAPTANS - Ismagilov F.R.; Akhmetov S.M.; Jexenov M.K.; Diarov M. (Academic Scientific Journal of Chemistry, 2020)
The paper examines methods of utilization of zeolite regeneration gases to assess the possibility of using them in an industrial adsorption unit for drying and purifying gases from hydrogen sulfide and mercaptans. The most promising is the method of decomposition of mercaptans to hydrogen sulfide and hydrogen on solid catalysts, which is carried out at a pressure and temperature of 200-350 °C, as well as the method of direct gas-phase catalytic oxidation of mercaptans with atmospheric oxygen. We carried out experiments on the purification of zeolite regeneration gases of the Orenburg GPP by oxidation with atmospheric oxygen using an iron oxide catalyst at a temperature of 180-250 °C. They showed that the gas purified from mercaptans contained elemental sulfur and disulfides as the main oxidation products, and 0.2% vol. of sulfur dioxide was present as a by-product. The method of purification from mercaptans and heavy hydrocarbon gases regeneration of composite adsorbent by thermocatalytic oxidation is also proposed. To reduce the yield of undesirable sulfur dioxide in the regeneration gas purified from mercaptans, it is proposed to divide the regeneration gas stream into two streams, while the larger part, comprising about 80-90% vol., is sent to oxidation on a zinc-iron catalyst at 200 °C, the second stream is mixed with oxidation products in a volume ratio in terms of mercaptans and sulfur dioxide equal to 1.5-2.2÷1, respectively, then the resulting mixture is passed at 160-200 °C through a titanium oxide catalyst with a gas volumetric velocity of 4000-6000 h-1. The proposed scheme for gas purification from mercaptans and heavy hydrocarbons on a composite adsorbent with oxidative regeneration makes it possible to carry out the subsequent process of amine purification of gas from hydrogen sulfide without the complications associated with foaming of the working solution. Furthermore, it becomes possible to transport gas purified from mercaptans and hydrogen sulfide through the pipeline without precipitation of condensate.